2023
DOI: 10.3390/plants12091733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genotype and Climate on Productive Performance of High Oleic Carthamus tinctorius L. under Rainfed Conditions in a Semi-Arid Environment of Sicily (Italy)

Abstract: Safflower (Carthamus tinctorius L.) is a promising oilseed crop for cultivation in central Southern Italy due to its high tolerance to drought and salinity stress and appreciable seed and oil yields. The genetic diversity of cultivars and climate factors can affect fatty acid composition and yield traits. This study aimed to assess the effects of genotype and climate conditions on the productive performance of eight high oleic safflower genotypes under rainfed conditions in Sicily (Italy). These genotypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…According to Sabzalian et al (2008) the linoleic acid ranged from 71.05% to 76.12%, oleic acid 12.24% to 15.43%, palmitic acid 5.48% to 7.59%, stearic acid 1.72% to 2.86%. Licata et al (2023) indicated that the linoleic, oleic, palmitic and stearic acid contents of safflower genotypes during two consecutive growing seasons were 16.6%-34.3%, 56.9%-74.2%, 5.6%-6.3% and 1.8%-2.3%, respectively. The results were found within the limits reported by these researchers.…”
Section: Fatty Acids Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to Sabzalian et al (2008) the linoleic acid ranged from 71.05% to 76.12%, oleic acid 12.24% to 15.43%, palmitic acid 5.48% to 7.59%, stearic acid 1.72% to 2.86%. Licata et al (2023) indicated that the linoleic, oleic, palmitic and stearic acid contents of safflower genotypes during two consecutive growing seasons were 16.6%-34.3%, 56.9%-74.2%, 5.6%-6.3% and 1.8%-2.3%, respectively. The results were found within the limits reported by these researchers.…”
Section: Fatty Acids Compositionmentioning
confidence: 96%
“…The 1000 seed weight is an important selection criterion that has an indirect effect on improving seed yield in safflower (Arslan, 2007a, b;Camaş & Esendal, 2006;Karimi et al, 2013;Mousavi Ojaq et al, 2020;Sirel & Aytac, 2016). Studies have shown that the 1000 seed weight in safflower varies between 24.7 and 47.8 g (Erbaş et al, 2016), 27.0 and 55.8 g (Arslan & Culpan, 2018), 21.7 and 53.1 g (Ali et al, 2020), 35.2 and 46.9 g (Arslan & Culpan, 2020), 38.0 and 41.0 g (Licata et al, 2023) and shows a wide variation. The 1000 seed weight obtained from autumn-sown compared to springsown is higher due to the long vegetative period (Oruç & Yilmaz, 2019).…”
Section: Seed Weightmentioning
confidence: 99%
“…Some winter-hardy accessions that can be sown in autumn and survive winter conditions were also reported in Australia (Cullerne et al, 2021). As a promising oilseed crop with appreciable seed and oil yields, it has shown great suitability in arid regions mainly due to its high tolerance to cold, drought and soil salinity, which allows its cultivation in regions that experience dry spells like central Southern Italy, Brazilian Cerrado, and Xinjiang of China (de Oliveira Neto et al, 2022;Licata et al, 2023). The wide adaptation ability of safflower is associated with its deep root system, which may take up moisture and nutrients, especially nitrogen that has been leached below the rooting zone of most other crops, especially in sandy soils which are already deprived of essential plant nutrients (Hussain and Al-Dakheel, 2018).…”
Section: Agronomic Conditions Of Safflower Cultivationmentioning
confidence: 99%